2007
DOI: 10.1152/ajpregu.00848.2006
|View full text |Cite
|
Sign up to set email alerts
|

Changes in environmental temperature influence leptin responsiveness in low- and high-fat-fed mice

Abstract: Loss of body fat in leptin-treated animals has been attributed to reduced energy intake, increased thermogenesis, and preferential fatty acid oxidation. Leptin does not decrease food intake or body fat in leptin-resistant high-fat (HF)-fed mice, possibly due to a failure of leptin to activate hypothalamic receptors. We measured energy expenditure of male C57BL/6 mice adapted to low-fat (LF) or HF diet and infused them for 13 days with PBS or 10 mug leptin/day from an intraperitoneal mini-osmotic pump to test w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…A key feature of cold-induced thermogenesis in normal animals is the increase in food intake that occurs over and above the increase in food intake necessary to support nutrition [3336]; as exemplified by the remarkable boost in food intake that occurs in lactating females exposed to the cold [26]. This suggests that central mechanisms controlling food intake, as related to nutrition, growth and body composition, may be independent of those associated with cold-induced thermogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…A key feature of cold-induced thermogenesis in normal animals is the increase in food intake that occurs over and above the increase in food intake necessary to support nutrition [3336]; as exemplified by the remarkable boost in food intake that occurs in lactating females exposed to the cold [26]. This suggests that central mechanisms controlling food intake, as related to nutrition, growth and body composition, may be independent of those associated with cold-induced thermogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Because the CD rats were tube fed, the increase in body fat mass was independent of a change in food intake, but energy expenditure was inhibited during the light phase in leptin-treated CD rats (18). The increase in body fat of leptin-treated rats is not limited to CD rats, as we had previously reported that a 12-day peripheral infusion of a physiological dose of leptin in mice fed a high-fat diet and housed in a warm environment increased body fat (19). We proposed that, although the high-fat diet prevented a leptin-induced inhibition of food intake, these mice were not totally leptin resistant and, in specific situations when leptin activity in the forebrain was inhibited, body fat would increase due to an inhibition of energy expenditure.…”
mentioning
confidence: 73%
“…In a previous study, we reported that high-fat-fed mice receiving peripheral infusions of leptin and housed in a warm environment (27°C) gained body fat mass when compared with their PBS-infused controls (19). We hypothesized that the increase in carcass fat was due to a partial leptin resistance that prevented leptin from reducing food intake and body fat combined with housing in an environment that prevented an increase in energy expenditure.…”
Section: Discussionmentioning
confidence: 98%
“…[44][45][46][47] In chronic studies, high-fat-fed mice studied in the TNZ actually gained additional fat when treated with leptin. 44 We are constantly faced with a myriad of variables that influence experimental outcomes, and our control of these conditions contributes to the ultimate validity of the findings. Even in the relatively simple experiment of injecting a drug and measuring a physiological variable, we must know and control T a .…”
Section: Pharmacological Studiesmentioning
confidence: 99%